English Language Teaching Development: Emergency Remote Teaching Challenges in the Covid-19 Era - Santiana, Santiana; Hikmatullah, Nanak; Pujasari, Ratu Sarah; Khan, Tariq; Ispina, Jacqueline Inting; Marzuki, Abdul Gafur (Institut Agama Islam Negeri Lhokseumawe, 2024)
To limit the spread of the Covid-19 virus, rapid modifications in instructional delivery transitioned from in-person to online education. The Covid-19 outbreak sparked a historic global push to learn and teach remote languages via Internet venues. The rapid transition from face-to-face to remote learning is significantly distinct from planned online learning. Due to a shortage of resources and preparation chances, both language teachers and students have quickly shifted to depending on online learning in the overwhelming majority of cases. Their tales demonstrate endurance, resourcefulness, and bravery under extremely difficult circumstances. Understanding the nature of this transition can help to advance Online Teaching (hereinafter OT) and Emergency Remote Teaching (hereafter ERT). This qualitative and descriptive study looks into the unexpected and radical changes in English ERT, with a focus on the conceptual framework for developing relevant and engaging ERT and student engagement during ERT. Several studies have been conducted in various regions of the world to investigate the methods and procedures created by English Language Teaching (hereinafter ELT) to help students strengthen their English language and literacy skills. These conceptual advances are studied and shown, as are the various ways how ELT responded to the difficulties raised. Different conceptual shifts necessitate a variety of ELT approaches to the challenges identified, which are demonstrated and addressed. This report summarises the investigation's primary findings and offers recommendations for teaching English remotely.